The Ukraine Crisis and Shift in us Foreign Policy - Woźniak, Michał (International Studies. Interdisciplinary Political and Cultural Journal, 2016)
War in Ukraine and the Russian annexation of Crimea are the events that changed the US policy towards Russia. The events in Ukraine forced the United States to take a closer look at Eastern and Central Europe. The United States’ policy during the Ukrainian crisis has been limited to sanctions and strong statements so far because in Ukraine there is an asymmetry of interests. Ukraine is much more important to Russia than to the United States. The United States may be willing to support the democratic and western aspiration of Ukrainians but will not risk a major conflict with Russia over it. However the crisis in Ukraine is not only about Ukraine or Russia. It is also about US credibility around the world. Both friends and foes are watching closely the American reaction to the situation. That is why the United States has increased its military presence in those NATO countries that share borders with Russia.